IMiPACT OF METHYL PARATHION ON LACTATE DEHYDROGENASE ISOZYMES OF A TELEOST TILAPIA MOSSAMBICA (PETERS) - Rao, K Sivaprasada; Ahmad, I Kabeer; Rao, K V Ramana (Indian Journal of Fisheries, 2011)
The electrophoretic patterns of lactate dehydrogenase showed varied distributionof the isozymes in four selected tissues of T. mossambica (Peters). Thestudies suggest that there are two sub-units which, on random comibination, giverise to five isozymes. The qualitative nature and mobility of the isozymatic patternsof each tissue remained unaltered except for a slight reduction in the intensityof bands under subacute methyl parathion toxicity. However, a decrease in quantitativelevels Of LDH, measured by colorimetry, corroborates a fall in intensityof all isozymes. The significance of the results are discussed in relation to physiologicalstress leading to a manifestation of phenomenon simulating anaerobiosis.